Sulforaphane in cancer precision medicine: from biosynthetic origins to multiscale mechanisms and clinical translation - Zhao, Zhipeng; Chen, Qianyue; Qiao, Xinyu; Wang, Jianjiang; Ali, Zaid Tala Abdulqader; Li, Jun; Yin, Ling (Frontiers in Immunology, 2025)
Sulforaphane (SFN), an isothiocyanate derived from glucoraphanin in cruciferous vegetables, has evolved from a dietary antioxidant to a sophisticated multi-target agent in oncology. While its roles in nuclear factor erythroid 2-related factor 2 (Nrf2) activation and histone deacetylase (HDAC) inhibition are well-established, this review provides a novel synthesis by integrating disparate research scales—a multiscale perspective that spans from the genetic and epigenetic regulation of glucoraphanin biosynthesis in plants to SFN’s recently elucidated effects on ferroptosis, cancer stem cells (CSCs), and the tumor immune microenvironment in humans. We critically evaluate how key host factors, such as gut microbiota composition and glutathione S-transferase (GST) polymorphisms, dictate SFN bioavailability and efficacy, thereby framing a precision nutrition paradigm for its application. Furthermore, we move beyond generic claims of synergy to detail SFN’s specific mechanisms in enhancing conventional therapies, including the modulation of drug transporters and immune checkpoints. By integrating advances from plant biochemistry to molecular oncology, this review establishes an updated and mechanism-oriented framework for realizing SFN’s compelling potential in cancer prevention and therapy through a precision medicine approach.